KUAT TEKAN BETON MUTU fc 30 DENGAN SUPERPLASTICIZERDAN AIR ENTRAINING AGENT - Fuadi, Darwisy (Universitas Negeri Surabaya, 2023)
Superplasticizer is an admixture added material that is mixed into the concrete mix and has been proven to improve concrete performance. Air Entraining Agent is a mixed additive in the form of a surfactant which creates very fine air bubbles with a diameter of 1/100mm2mm, which can improve the properties of concrete because the air bubbles function as lubricating oil. Air Entraining Agent increases the yield stress point, buildability, overall 3D printability of concrete compared to the same mix that does not contain Air Entraining Agent.Testing and Experiment Methods in this study were carried out by making samples of test objects and testing concrete in the materials laboratory of PT Solusi Bangun Beton Indonesia. The number of test objects used is 8 test objects, in the form of cylindrical concrete with their respective compositions which will be tested every 28. In addition, study data from SNI and foreign standards such as ASTM can also be studied.Test results of normal concrete compressive strength of quality concrete cylindersf’c 30 MPa has an average weight of 12.325 kg and an average compressive strength of 41.25. The results of testing the compressive strength of concrete with the addition Superplasticizer0.4% And Air Entraining Agent 0.02% quality concrete cylinderf’c 30 MPa has an average weight of 12.265 kg, and an average compressive strength of 31.90. The results of testing the compressive strength of concrete with the addition Superplasticizer0.4% And Air Entraining Agent 0.007% quality concrete cylinderf’c 30 MPa has an average weight of 11.625 kg, and an average compressive strength of 28.50. The results of testing the compressive strength of concrete with the addition Superplasticizer0.4% And Air Entraining Agent 0.011% quality concrete cylinderf’c 30 MPa has an average weight of 11.415 kg, and an average compressive strength of 27.30.